Goethe's "Faust" Seven Essays - Cottrell, Alan P. (The University of North Carolina Press, 1976)
The essays in this collection range from close textual analysis to discussions of larger problems such as Goethe's relation to Christianity as illuminated by the theme of sacrifice in Faust. This work is viewed with particular reference to Goethe's natural scientific epistemology and to the problems confronting Western man in our own times. A study of Faust's blindness and the inner light complete the collection.